The Influence of Leadership Performance on Employee Commitment which is moderated by Turnover Intention - Asri, Cahya Purnama (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2024)
This research examines the analysis of the influence of performance and leadership on employee commitment moderated by turn over intention Study on Companies in Yogyakarta . This research was conducted at a company in Yogyakarta, the sample used in this research was 60, and the analysis tool used was SPSS as the tool . Is there a positive influence between Performance and Employee Commitment, is there a positive influence between Leadership and Employee Commitment, is there a positive influence between Performance and Employee Commitment in Companies in Yogyakarta which is Moderated by Turn Over Intention , is there a positive influence Between Leadership and Employee Commitment to Companies in Yogyakarta which is Moderated by Turn Over Intention .